Selection methodology of mechanical drive system servomotor and transmission through transient power analysis - Otero Yugat, Jesús (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In many industrial processes, are increasingly mechanical drives to be made in a very short time, causing the driving force is used to speed up or slow down the inertia of the system, and not to provide the power required by the receptor. This paper presents a methodology for selecting the servomotor and transmission suitable for a conventional mechanical drive system. It has used a mapping analysis supported by diagrams P'-W, which relate the transient power system regarding its kinetic energy. As an illustration, a situation of industrial application is presented.